Educational support social entrepreneurship - M. A. Petrova (Путеводитель предпринимателя, 2020)
In modern world, the educational support of social entrepreneurship is one of the most widely discussed topics. The development of social entrepreneurship in Russia today is becoming increasingly important and popular, being a special kind ofsocially oriented economic activities. Through educational support and wide media coverage of social entrepreneurship and specific social projects can involve a large number of people together who can make real breakthroughs and to contribute to the reform areas of public life.